Women’s learning: A kaleidoscope - Daniele D. Flannery; Elisabeth Hayes (Adult Education Research Conference, 1996)
The purpose of this study was to identify and synthesize themes from dissertations of women’s learning in settings other than those where women are students in higher education. One theme is explicated briefly to demonstrate the richness of the themes.